Trauma vicariante, Síndrome de Burnout e satisfação por compaixão: um estudo com magistrados - Silva, Priscila Netto de Campos da (2020)
When coming into contact with the suffering of others, professionals who provide care and support to trauma victims are exposed both to favorable situations capable of providing high levels of satisfaction, and to unfavorable situations that cause negative symptoms. Therefore, they may develop chronic stress and /or vicarious trauma that can directly affect their physical, mental and social health. This study aimed at investigating the presence of vicarious trauma (TV), Compassion Satisfaction (SC) and Burnout Syndrome (SB) in magistrates of three specialized courts in Greater São Paulo. The survey involved 97 magistrates. Data collection instruments were the ProQol-IV BR and the Maslach Burnout Inventory (MBI) to assess Compassion satisfaction, vicarious trauma and burnout. The Holmes and Rahe Scale was also applied to measure the loads of stressful events caused by the external events experienced by the participants in the last year. The findings revealed that 70.1% of the participants have moderate to high levels of Compassion satisfaction, 75.3% have moderate/high levels of symptoms of burnout, and 36% of the sample has high levels of vicarious trauma. In addition, 84.5% have low professional achievement and 69% have moderate/high levels of emotional exhaustion and depersonalization. Results also indicated that cases involving violence are the ones that most affect the magistrates emotionally and that the family and social network are the most used resources to cope with work stress. These findings validate the present study initial theoretical propositions and indicate an opportunity for further studies on the subject, in order to expand the repertoire of solutions in favor of improving magistrates' quality of life